A viscosity bio-reducer for extra-heavy crude oil. (17th January 2018) - Suárez-Domínguez, E.J.; Pérez-Sánchez, J.F.; Palacio-Pérez, A.; Rodríguez-Valdes, A.; Izquierdo-Kulich, E.; González-Santana, S.
ABSTRACT: Considering that high viscosity of extra-heavy crudes is related to the formation of a dispersed phase of asphaltenes, a dynamic interaction model is proposed which explains the mechanism to achieve viscosity reduction based on the molecular interacting energies between the ester active principle of a viscosity bio-reducer and the asphaltene fraction of crude oil. A qualitative comparison is made between the theoretical and experimental results observed in relation to the rheological behavior of Mexican extra-heavy crudes in the presence of the enhancer. Both, theoretical and experimental data, described a decrease in the asphaltenes dispersed fraction in relation to the ester concentration mainly because of polarity in asphaltenic crudes.